SYNTAX scale estimates of coronary stenosis severity and outcomes of various revascularisation strategies in patients with ST segment elevation myocardial infarction and multi-vessel coronary pathology - R. S. Tarasov; V. I. Ganyukov; P. A. Shushpannikov; P. A. Krotikov; O. L. Barbarash; L. S. Barbarash (Российский кардиологический журнал, 2013)
Aim. To assess 30-day and long-term outcomes of various revascularisation strategies in patients with myocardial infarction and ST segment elevation (STEMI) and multi-vessel coronary pathology (MVCP), in regard to the severity of coronary stenosis, as assessed by the SYNTAX scale. Material and methods. The 30-day and long-term outcomes of various strategies of primary percutaneous coronary intervention (PCI) were assessed in 227 STEMI patients, in regard to the severity of their coronary stenosis (as assessed by the SYNTAX scale). Group 1 included 40 patients who underwent multi-vessel stenting (MVS) as a part of their primary PCI, while Group 2 included 187 patients with indications for staged revascularisation (SR). Results. At baseline, the MVS and SR subgroups with severe coronary stenosis (SYNTAX score